2021
DOI: 10.1155/2021/8828410
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity: A Major Setback in Childhood Leukemia Treatment

Abstract: Ongoing research in the field of pediatric oncology has led to an increased number of childhood cancer survivors reaching adulthood. Therefore, ensuring a good quality of life for these patients has become a rising priority. Considering this, the following review focuses on summarizing the most recent research in anthracycline-induced cardiac toxicity in children treated for leukemia. For pediatric cancers, anthracyclines are one of the most used anticancer drugs, with over half of the childhood cancer survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
0
13
0
3
Order By: Relevance
“…Oxidative stress is a central mechanism in doxorubicin-induced cardiac dysfunction, as doxorubicin increases the mitochondrial production of ROS with the accumulation of ROS in the myocardium, leading to DNA and protein damage, membrane lipid peroxidation, and mitochondrial dysfunction. 3,20,31 In addition, the myocardium has a moderately low level of antioxidant defenses and is highly susceptible to doxorubicin-induced cytotoxicity through oxidative stress. 32 In the present study, the cardiotoxicity of doxorubicin was evaluated by echocardiography and biochemical markers of cardiac injury including TPI, CK-MB, and NT-proBNP, which are markers of myocardial cell injury, ventricular dysfunction, and cardiomyocytes necrosis of different etiologies including doxorubicin-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative stress is a central mechanism in doxorubicin-induced cardiac dysfunction, as doxorubicin increases the mitochondrial production of ROS with the accumulation of ROS in the myocardium, leading to DNA and protein damage, membrane lipid peroxidation, and mitochondrial dysfunction. 3,20,31 In addition, the myocardium has a moderately low level of antioxidant defenses and is highly susceptible to doxorubicin-induced cytotoxicity through oxidative stress. 32 In the present study, the cardiotoxicity of doxorubicin was evaluated by echocardiography and biochemical markers of cardiac injury including TPI, CK-MB, and NT-proBNP, which are markers of myocardial cell injury, ventricular dysfunction, and cardiomyocytes necrosis of different etiologies including doxorubicin-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…DCT is described as earlyonset toxicity if cardiac manifestations occurred within 1 year of ending the chemotherapy, and it is considered as late-onset toxicity if cardiac symptoms appeared after more than 1 year of stopping chemotherapy. 3,4 Several mechanisms have been implicated in the pathophysiology of DCT, such as apoptosis, mitochondrial dysfunction, and increased oxidative stress. However, the main pathophysiological mechanism of DCT is suggested to be related to oxidative stress and increased production of intracellular reactive oxygen species (ROS) in cardiomyocytes, leading to abnormalities in cardiac contractile function and myocardial cell injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, both I and T cardiac troponins were shown to have an important prognostic role, being able to predict up to 3 months ahead the development of a decrease in LVEF, but there is still important controversy regarding this topic. As several studies demonstrated the role of elevations of high-sensitive cardiac troponin-I in predicting subclinical cardiomyocyte damage, other small studies proved a very low sensitivity for subclinical heart disease when troponin T was used [ 60 , 61 ]. What is more, as hs-cTnI levels can be elevated in up to 13.1% of healthy children, many studies suggest the need of using adjusted cuts-off values for this patients [ 62 ].…”
Section: Cardiac Troponins: From Promising To Gold Standardmentioning
confidence: 99%
“…One of the most concerning side effects of CT is cardiotoxicity which can vary from subclinical myocardial dysfunction to irreversible and often fatal heart failure [ 45 ]. It is induced in a dose-dependent manner primarily by anthracyclines which are widely used for therapeutic intervention in probably more than 50% of all childhood cancer patients posing them with an elevated risk for cardiomyopathies in their later life [ 46 ].…”
Section: Cancer Therapies and Risks Of Second Primary Malignanciesmentioning
confidence: 99%